Application of a Photocatalyst as an Inactivator of Bovine Coronavirus - Nobuki Yoshizawa; Ryoko Ishihara; Daisuke Omiya; Midori Ishitsuka; Shouichirou Hirano; Tohru Suzuki (Viruses, 2020)
Bovine coronavirus (BCoV), a major causative pathogen of bovine enteric and respiratory diseases and a zoonotic pathogen transmissible between animals and humans, has led to severe economic losses in numerous countries. BCoV belongs to the genus Betacoronavirus, which is a model of a pathogen that is threatening human health and includes severe acute respiratory syndrome coronavirus (SARS-CoV), SARS-CoV-2, and Middle East respiratory syndrome coronavirus. This study aimed to determine whether photocatalytic material effectively reduces CoVs in the environment. Using the film adhesion method of photocatalytic materials, we assessed its antiviral activity and the effect of visible light irradiation according to methods defined by the International Organization for Standardization. Consequently, photocatalytic material was found to have antiviral activity, reducing the viral loads by 2.7 log TCID50 (tissue culture infective dose 50)/0.1 mL (500 lux), 2.8 log TCID50/0.1 mL (1000 lux), and 2.4 log TCID50/0.1 mL (3000 lux). Hence, this photocatalytic material might be applicable not only to reducing CoVs in the cattle breeding environment but also perhaps in other indoor spaces, such as offices and hospital rooms. To our knowledge, this study is the first to evaluate the antiviral activity of a photocatalytic material against CoV.